Anthroposcreens : mediating the climate unconscious - Leyda, Julia (Cambridge elements. Elements in environmental humanities, 2023)
Anthroposcreens frames the 'climate unconscious' as a reading strategy for film and television productions during the Anthropocene. Drawing attention to the affects of climate change and the broader environmental damage of the Anthropocene, this study mobilizes its frame in concert with other tools from cultural and film studies-such as debates over Black representation-to provide readings of the underlying environmental themes in Black American and Norwegian screen texts. These bodies of work provide a useful counterpoint to the dominance of white Anglo-American stories in cli-fi while also ranging beyond the boundaries of the cli-fi genre to show how the climate unconscious lens functions in a broader set of texts. Working across film studies, cultural studies, Black studies, and the environmental humanities, Anthroposcreens establishes a cross-disciplinary reading strategy of the 'climate unconscious' for contemporary film and television productions. This title is also available as Open Access on Cambridge Core.